Booker T. Washington - Gosda, Randy T., 1959- (Edina, Minn. : Abdo, 2002)
A biography of one-time slave, known for his commitment to education and his role in establishing Tuskegee Institute.
Includes index.
3.8
K-3
Keywords: Washington, Booker T., -- 1856-1915 -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Educators -- United States -- Biography -- Juvenile literature; Washington, Booker T., -- 1856-1915.; Educators; African Americans -- Biography; Washington, Booker T., -- 1856-1915.; Educators -- United States -- Biography; African Americans -- Biography